Mapping Student Learning Styles Achieving Using Kolb's Learning Style Inventory in Sinjai Regency - A. Octamaya Tenri Awaru; Muhammad Syukur; Andi Dodi May Putra Agustang; Zainal Arifin (Jurnal Ad'ministrare, 2020)
Learning style is one of the factors supporting student achievement. Learning style is one of the factors that influence learning achievement that comes from within the individual. Children who do not understand their learning styles will find it difficult to master the material well and will affect their learning outcomes. This research was conducted in Sinjai Regency with the object of research being students with achievement, namely students who were ranked 1st, 2nd, and 3rd in their study groups. The purpose of this study was to map the learning styles of high school students in Sinjai Regency. This type of research is a quantitative descriptive study. The population is 240 outstanding students from 4 schools in Sinjai Regency. The sample is 62 people or 25 percent of the study population. The data collection techniques used were questionnaires and documentation. The data analysis used in this study was a descriptive statistical analysis of the percentages used to examine the research variables, namely the learning styles and social relationships of outstanding students. The results of this study found the learning styles of high school achievement students in Sinjai Regency, namely the Converger learning style type as many as 35 students or 56.5 percent, the accommodator learning style type were 16 students or 25.8 percent, the assimilator learning type was 7 students or 11.3 percent and the type of learning diverger as many as 4 people or 6.5 percent of the 62 respondents who are outstanding students or are ranked 1-3 in the study group. From the research results, it appears that the type of learning style that dominates or excels the respondent is the convergent learning style, which is a quadrant combination of thinking and doing. Converger type people have good skills in problem-solving and decision making. Use logic in the face of problems and like hands-on practice. Take challenges as opportunities. The results of his observations were collected and then used as a theory